Microwave-assisted synthesis of functionalized spirohydantoins as 3-D privileged fragments for scouting the chemical space. Issue 26 (29th June 2016) - Prevet, Hugues; Flipo, Marion; Roussel, Pascal; Deprez, Benoit; Willand, Nicolas
Graphical abstract: Highlights: Rapid chemical pathway for the synthesis of new 3D privileged fragments. Microwave-assisted synthesis of a large set of spirohydantoins. Selective N-monoalkylation of the hydantoin ring to access functionalized analogs. Abstract: Fragment-based drug design has been successfully applied to a large set of proteins, however in order to expand this concept to the most demanding targets, such as protein–protein interactions, it is required to enrich current fragment libraries with new and original 3D privileged fragments. Our goal was to develop a rapid microwave-assisted synthesis of 27 new privileged spirohydantoin fragments. Among them 24 compounds showed a high water solubility. These molecules were plotted according to the normalized principal moments of inertia of their minimized conformers, and most of the compounds were prone to occupy under-populated regions of the triangular plot. Finally we demonstrated that the hydantoin ring can be selectively N -monoalkylated providing the access to rapid functionalization for further elaboration.